Exploring Dynamics Communications and Media Acceptance Through Digital Media Platform from Korean Community Perspective - Minseo, Kim; Khalid, Mutia Anggeraini Binti (Electronic Journal of Business and Management, 2024)
This study focuses the acceptance of media in relation to traditional and digital media among Korean Community in Seoul. It observes on the acceptance, quality and trustworthy of this information that are distributed on these platforms. The research is based on qualitative research method that applies induction techniques. A multiple case study is implemented with participants from Seoul. A “Korean’s Community Media Acceptance Model” is derived as to provide an insight on the factors that could play important roles on media acceptance within societies.